Irrigation of wheat with select hydraulic fracturing chemicals: Evaluating plant uptake and growth impacts. (15th March 2021) - Shariq, Linsey; McLaughlin, Molly C.; Rehberg, Rachelle A.; Miller, Hannah; Blotevogel, Jens; Borch, Thomas
Abstract: Oilfield flowback and produced water (FPW) is a waste stream that may offer an alternative source of water for multiple beneficial uses. One practice gaining interest in several semi-arid states is the reuse of FPW for agricultural irrigation. However, it is unknown if the reuse of FPW on edible crops could increase health risks from ingestion of exposed food, or impact crop growth. A greenhouse experiment was conducted using wheat ( Triticum aestivum) to investigate the uptake potential of select hydraulic fracturing additives known to be associated with health risks. The selected chemicals included acrylamide, didecyldimethylammonium chloride (DDAC), diethanolamine, and tetramethylammonium chloride (TMAC). Mature wheat grain was extracted and analyzed by liquid chromatography-triple quadrupole mass spectrometry (LC-QQQ) to quantify chemical uptake. Plant development observations were also documented to evaluate impacts of the chemicals on crop yield. Analytical results indicated that TMAC and diethanolamine had significantly higher uptake into both wheat grain and stems than control plants which were not exposed to the four chemicals under investigation. Acrylamide was measured in statistically higher concentrations in the stems only, while DDAC was not detected in grain or stems. Growth impacts included lodging in treated wheat plants due to increased stem height and grain weight, potentially resulting from increased nitrogen application. While analytical results show that uptake of select hydraulic fracturing chemicals in wheat grain and stems is measurable, reuse of FPW for irrigation in real world scenarios would likely result in less uptake because water would be subject to natural degradation, and often treatment and dilution practices. Nonetheless, based on the outstanding data gaps associated with this research topic, chemical specific treatment and regulatory safeguards are still recommended. Graphical abstract: Graphical abstract showing didecyldimethylammounium chloride remaining in the soil, acrylamide being taken up into the wheat stem, and diethanolamine and tetramethylammonium chloride being taken up into the wheat stem and grain. Image 1 Highlights: Wheat plants are capable of taking up certain hydraulic fracturing chemicals into stems and grain. Over 30 hydraulic fracturing chemicals are physiochemically similar to those taken up by wheat plants in this experiment. Excess nitrogen from the additive hydraulic fracturing chemicals impacted wheat growth and yield. Liquid chromatography-triple quadrupole mass spectrometry effectively quantifies hydraulic fracturing chemicals in wheat. Flowback and produced water destined for food crop irrigation requires treatment to prevent toxicity. Abstract : Hydraulic fracturing chemicals can accumulate in edible parts of food crops and impact plant growth characteristics.